The Influence of Educational Leadership and Islamic Leadership on Teacher Performance with Organizational Culture as A Moderating Variable at SD Negeri 2 Sulusuban - Wahyu Febriana; Syafrimen Syafrimen; Tulus Suryanto; Koderi Koderi (Assyfa Journal of Islamic Studies, 2026)
Principal leadership and organizational culture are key factors influencing teacher performance in elementary schools. This study aims to examine the direct influence of educational leadership and Islamic leadership on teacher performance, as well as the indirect influence through organizational culture as a moderating variable. The research location was SD Negeri 2 Sulusuban with a population of 32 teachers. The method used was quantitative with Moderated Regression Analysis (MRA). Data were collected through a Likert scale questionnaire (1–5) that had been tested for validity and reliability. The results showed that educational leadership has a significant positive effect on teacher performance. Islamic leadership also has a significant positive effect. Organizational culture was proven to moderate the influence of educational leadership on teacher performance, but did not moderate the influence of Islamic leadership. The R Square value of 0.732 indicates that 73.2% of the variation in teacher performance can be explained by the model. This study recommends strengthening collaborative organizational culture to maximize the impact of educational leadership on teacher performance, as well as strengthening Islamic leadership values directly.